2014
DOI: 10.1177/0300985814540543
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Neuropathology of Ovine Enterotoxemia Produced by Clostridium perfringens Type D Wild-Type Strain CN1020 and Its Genetically Modified Derivatives

Abstract: Clostridium perfringens type D causes enterotoxemia in sheep and goats. The disease is mediated by epsilon toxin (ETX), which affects the cerebrovascular endothelium, increasing vascular permeability and leading to cerebral edema. In the present study, we compared the distribution and severity of the cerebrovascular changes induced in lambs by C. perfringens type D strain CN1020, its isogenic etx null mutant, and the ETX-producing complemented mutant. We also applied histochemical and immunohistochemical marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 26 publications
2
38
0
Order By: Relevance
“…Consistent with the latter two hypotheses, ultrastructural loss of a recognisable Golgi structure is a likely early event in EGS, and EGS is associated with major perturbations in the cytoskeleton of autonomic neurons that result in the accumulation of dopamineb-hydroxylase and presynaptic proteins in neuronal perikarya [19,27,28]. b-APP has been described as a marker of early axonal injury prior to apparent histological changes in routine H&E-stained sections [29].…”
Section: Discussionmentioning
confidence: 70%
“…Consistent with the latter two hypotheses, ultrastructural loss of a recognisable Golgi structure is a likely early event in EGS, and EGS is associated with major perturbations in the cytoskeleton of autonomic neurons that result in the accumulation of dopamineb-hydroxylase and presynaptic proteins in neuronal perikarya [19,27,28]. b-APP has been described as a marker of early axonal injury prior to apparent histological changes in routine H&E-stained sections [29].…”
Section: Discussionmentioning
confidence: 70%
“…The CNS manifestations of C. perfringens type D-mediated disease are wholly dependent on ε-toxin, since targeted loss of function of the ε-toxin gene renders the organism incapable of causing CNS pathology, and restoration of a functional ε-toxin gene reestablishes the CNS phenotype (6, 7). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has also been demonstrated that the rabbit colon is also sensitive to the action of purified CPE, with both fluid secretion and mucosal damage observed (Garcia et al, 2014). The histological changes caused by CPE in both small intestinal and colonic loops of rabbits consist mainly of mucosal necrosis and hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…The histological changes caused by CPE in both small intestinal and colonic loops of rabbits consist mainly of mucosal necrosis and hemorrhage. These changes are both time- and dose-dependent (Duncan et al, 1968; McDonel and Duncan, 1975, Smedley 3 rd et al, 2008; Garcia et al, 2014) and begin at villus tips in small intestinal loops (McDonel and Duncan, 1975, Sherman et al, 1994), where there is a greater density of claudin 4 (Smedley 3 rd et al, 2008). Rabbits have also been used to study the binding of CPE to extraintestinal tissues, which led to the demonstration that this toxin binds to liver and kidney (McDonel, 1980), a finding that might explain systemic changes in patients with enterotoxigenic C. perfringens type A-associated disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation